Regional Cluster Analysis in East Java Province Based on Non-Communicable Disease Using Fuzzy C-Means - Handayani, Dwi; Fasya, Abdul Hakim Zakkiy; Ibad, Mursyidul; Budiarti, Tamara Nur (Universitas Nahdlatul Ulama Surabaya, 2024)
East Java has a prevalence of NCD exceeding the national average. Limited information on the disease clustering makes less optimal policy-making for preventing and controlling. This study aims to cluster areas and identify NCD risk factors. The study used secondary data from Basic Health Research in 2018. The data was analyzed using FCM. There were 3 clusters resulting from this research. In Cluster 1, the average proportion of all NCD's and 33.33% of the NCD's risk factors exceeds the average proportion of the province. In Cluster 2, the average proportion of 1 NCD and 77.78% of the NCD's risk factors exceeds the average proportion of the province. In Cluster 3, all NCD's have an average proportion less than the average proportion in the province and 22.22% of the NCD's risk factors have an average proportion exceeding the average proportion in the province. Cluster 1 is the cluster with the average proportion of NCD's exceeding the average proportion of NCD's in the province and the highest among the other clusters. Cluster 2 is a cluster with an area with risk factors for NCD's with the highest average proportion of the different clusters. Keywords: NCDs, analysis cluster, fuzzy c-means